Menyuarakan Teologi Tubuh dalam Budaya Pornografi - Yeremia Yordani Putra; Yohanes Krismantyo Susanta (Reformed Center for Religion and Society, 2021)
Pornography is a culture that develops rapidly along with advances in science and technology. In fact, pornography is considered as something common and has become a commercial commodity an economic value. Looking at this reality, a deep theological reflection is needed in order to improve the paradigm and praxis of the body and sexuality understanding. By using literature research, this paper shows that pornography has distorted people’s understanding of sexuality and their perceptions of fellow humans. The idea and act of objectifying the body for one’s own pleasure has been valid and is something considered right by society. Therefore, this paper offers a theology of the body as an effort to revise the wrong perspective of the body. The body is not just a body, but the entire existence of a human being which but also has a personal and spiritual identities.